Pengaruh Servant Leadership Terhadap Employee Affective Well-Being dengan Mediasi Personal Growth dan Perceived Organizational Support - Dimas Prabowo, Muhammad; Nugroho, Sukmo Hadi (Universitas Trunojoyo Madura, 2024)
The role of a leader is very necessary, with the hope that employees can also be involved in dealing with company problems that are experiencing a decline in performance. This research aims to determine the influence of servant leadership on employee affective well being, both directly and indirectly through the mediation of personal growth and perceived organizational support. This research is a development of previous research conducted on service management. Respondents were taken using purposive sampling. Data collection was carried out by distributing questionnaires to 140 employees. The data analysis technique used is the Lisrel Structure Question Modeling (SEM) analysis technique. The research results show that servant leadership is directly related to employee affective well being. Apart from that, servant leadership can be related to employee affective well being, so it will be mediated using personal growth and perceived organizational support. It is hoped that the contribution in the research will provide insight into science in human resource management and can become a new reference for Medical Device companies.